Use of laser therapy in the postoperative period of colocephalectomy in dogs - Borges, Raieli Luana; Reichert , Bruna Bogorni; da Silva, Tanara Raquel de Oliveira; Wilges, Carlos Henrique de Mello (Seven Editora, 2024)
For a better postoperative rehabilitation of colocephalectomy in dogs, laser therapy has been shown to be an alternative modality that is being considered efficient because it is safe, painless, regenerative and improves animal welfare. This therapy uses low-level laser that positively assists in the healing process, presenting analgesic, anti-inflammatory, healing and circulatory effects. The laser used is therapeutic, being a coherent, monochromatic and collimated light source, for this reason it does not present side effects when used at the correct power. Hip dysplasia is described as an impairment of the hip joint, and is considered one of the most important orthopedic dysfunctions in large and giant dogs, and can present in different degrees and different forms of joint degeneration. It manifests itself through specific clinical signs, which contribute to a conclusive diagnosis. The treatment of hip dysplasia has as its main objective pain control, its indication is variable according to factors related to each patient, and can be conservative or surgical, as is the case with colocephalectomy. DOI:https://doi.org/10.56238/sevened2024.026-009